Factors Affecting Adaptability of Cryptocurrency: An Application of Technology Acceptance Model - Sagheer, Nadia; Khan, Kanwal Iqbal; Fahd, Samar; Mahmood, Shahid; Rashid, Tayyiba; Jamil, Hassan (Frontiers in Psychology, 2022)
Cryptocurrency has revolutionized the economic system of the world. It provides a new and innovative means of exchange. Blockchain-based digital currencies such as Bitcoin, Ethereum, and Lite coin have revolutionized the world's economic system. It provides the new and innovative means of exchange that has speedily invaded the financial market trends and changed the traditional cash worldand changed the strength of the world’s economy. However, consumers have low acceptability for these technologies blockchain-based cryptocurrency due to increasing online scams and the absence of a regulatory framework. There is also a misconception regarding about its usage on many platforms, which has created a clear gap in the literature to address this issue. Therefore, Thisthe current study intends to estimate investigate the effect of technology awareness on the behavioural intention of crypto users towards blockchain-based digital currencies through perceived factors (usefulness, risk, and ease of use, risk). It also empirically examines the moderating role of government support on these indirect paths. The It empirically examines the underlying framework is investigated by surveying 333 respondents, targeting from the Z generation. Results revealed that perceived factors (usefulness, ease of use, riskusefulness, risk, and ease of use) mediate the relationship between technology awareness and behavioural intention. Furthermore, government support strengthens the indirect relationship of technology awareness on behavioural intention through technology acceptance determinants, such that the effect of technology awareness on behavioural intention through perceived factors (usefulness, ease of use, riskusefulness, risk, and ease of use) is more assertive when government support is high. The findings will provide a new dimension to different financial bodies, implementing monetary policy, and highlight the need to adopt innovative digital technologies in Pakistan.